Pelatihan Pembuatan Preparat Segar Bagi Guru Biologi Sekolah Menengah Atas - Welsiliana Welsiliana; Gede Arya Wiguna; Florian Mayesti Prima Remba Makin; Ite Morina Yostianti Tnunay; Lukas Pardosi; Dicky Frengky Hanas (Society : Jurnal Pengabdian Masyarakat, 2023)
Learning media is anything that can be used to convey messages or information in the teaching and learning process so that it can stimulate students' attention and interest in learning. One of the media in biology learning is preparation. Preparations are preparations in the form of organs, tissues, cells, and or bodies of organisms that are preserved or fresh so as to provide convenience for studying, observing, or researching. The purpose of this service activity is to provide training to make fresh preparations for high school biology teachers. The results of this activity include presentation of material on preparations, training on making fresh preparations, and observing fresh preparations that have been made under a microscope. This activity provides new and practical experiences for biology teachers and increases knowledge and enthusiasm for doing simple practicals